Examining food waste behaviour and its influencing factors among UiTM Terengganu students - Khazali, Nur Fatin Amirah; Zahari, Harnizam; Zain, Razlan Adli; Abdullah, Rahman (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
Food waste remains a major global challenge to environmental sustainability, with young consumers often contributing due to poor meal planning and limited awareness of waste-reduction practices. Among students, it is further driven by convenience and tight budgets. This study explored food waste behaviour among UiTM Terengganu students, examining the influence of attitudes, subjective norms, perceived behavioural control, and personal norms. Using a quantitative, cross-sectional, correlational design, data were collected through a structured questionnaire from students living in dormitories or rented houses via simple random sampling. Descriptive statistics and Pearson correlations revealed that food waste behaviour was moderately and negatively related to subjective norms (r = −0.273, p < 0.01) and perceived behavioural control (r = −0.239, p < 0.01), and weakly and negatively related to personal norms (r = −0.120, p < 0.05). Attitude was moderately correlated with subjective norms (r = 0.429, p < 0.01), strongly with perceived behavioural control (r = 0.510, p < 0.01), and most strongly with personal norms (r = 0.572, p < 0.01). Subjective norms were strongly associated with perceived behavioural control (r = 0.686, p < 0.01) and moderately with personal norms (r = 0.509, p < 0.01), while perceived behavioural control showed a strong link with personal norms (r = 0.672, p < 0.01).